Intriguing Humans and Primates chromosomes 4 - Jean-claude PEREZ (Journal of Primates, 2018)
The global analysis of 3 human genomes of increasing levels of evolution (neanderthal / sapiens build34 of 2003 / sapiens hg38 of 2013) reveals 2 levels of numerical constraints controlling, structuring and optimizing the DNA sequences of these genomes. A global constraint - which we will call
Keywords: Primates